Genomic insight into Campylobacter jejuni isolated from commercial turkey flocks in Germany using whole-genome sequencing analysis - El-Adawy, Hosny; Hotzel, Helmut; García-Soto, Silvia; Tomaso, Herbert; Hafez, Hafez M.; Schwarz, Stefan; Neubauer, Heinrich; Linde, Jörg (Frontiers in Veterinary Science, 2023)
Campylobacter (C.) jejuni is a zoonotic bacterium of public health significance. The present investigation was designed to assess the epidemiology and genetic heterogeneity of C. jejuni recovered from commercial turkey farms in Germany using whole-genome sequencing. The Illumina MiSeq® technology was used to sequence 66 C. jejuni isolates obtained between 2010 and 2011 from commercial meat turkey flocks located in ten German federal states. Phenotypic antimicrobial resistance was determined. Phylogeny, resistome, plasmidome and virulome profiles were analyzed using whole-genome sequencing data. Genetic resistance markers were identified with bioinformatics tools (AMRFinder, ResFinder, NCBI and ABRicate) and compared with the phenotypic antimicrobial resistance. The isolates were assigned to 28 different sequence types and 11 clonal complexes. The average pairwise single nucleotide-polymorphisms distance of 14,585 SNPs (range: 0–26,540 SNPs) revealed a high genetic distinction between the isolates. Thirteen virulence-associated genes were identified in C. jejuni isolates. Most of the isolates harbored the genes flaA (83.3%) and flaB (78.8%). The wlaN gene associated with the Guillain–Barré syndrome was detected in nine (13.6%) isolates. The genes for resistance to ampicillin (blaOXA), tetracycline [tet(O)], neomycin [aph(3')-IIIa], streptomycin (aadE) and streptothricin (sat4) were detected in isolated C. jejuni using WGS. A gene cluster comprising the genes sat4, aph(3′)-IIIa and aadE was present in six isolates. The single point mutation T86I in the housekeeping gene gyrA conferring resistance to quinolones was retrieved in 93.6% of phenotypically fluoroquinolone-resistant isolates. Five phenotypically erythromycin-susceptible isolates carried the mutation A103V in the gene for the ribosomal protein L22 inferring macrolide resistance. An assortment of 13 β-lactam resistance genes (blaOXA variants) was detected in 58 C. jejuni isolates. Out of 66 sequenced isolates, 28 (42.4%) carried plasmid-borne contigs. Six isolates harbored a pTet-like plasmid-borne contig which carries the tet(O) gene. This study emphasized the potential of whole-genome sequencing to ameliorate the routine surveillance of C. jejuni. Whole-genome sequencing can predict antimicrobial resistance with a high degree of accuracy. However, resistance gene databases need curation and updates to revoke inaccuracy when using WGS-based analysis pipelines for AMR detection.